Acute Kidney Injury in Children with Acute Appendicitis - Pierluigi Marzuillo; Crescenzo Coppola; Roberta Caiazzo; Giulia Macchini; Anna Di Sessa; Stefano Guarino; Francesco Esposito; Emanuele Miraglia del Giudice; Vincenzo Tipo (MDPI AG, 2022)
We hypothesized that-as in other common pediatric conditions-acute appendicitis (AA) could be complicated by acute kidney injury (AKI). We aimed to investigate the prevalence of, and the factors associated with AKI in a cohort of patients with AA. We retrospectively collected data of 122 children (63.9% of male gender; mean age 8.6 ± 2.9 years; range: 2.2-13.9 years) hospitalized for AA. AKI was defined according to the Kidney Disease/Improving Global Outcomes creatinine criteria. We considered a basal serum creatinine value as the value of creatinine estimated with the Hoste (age) equation, assuming that the basal estimated glomerular filtration rate (eGFR) was 120 mL/min/1.73 m2. Explorative univariate logistic regression analysis was used to explore the associations with AKI. Out of 122 patients, nine (7.4%) presented with AKI. One patient had stage two AKI and the remaining had stage one AKI. The maximum AKI stage was found at admission. The patients with AKI showed a higher prevalence of fever ≥ 38.5 °C (p = 0.02), vomiting (p = 0.03), ≥5% dehydration (p = 0.03), and higher levels of both C-reactive protein (CRP) (p = 0.002) and neutrophils (p = 0.03) compared with patients without AKI. Because all patients with AKI also presented with vomiting, an Odds Ratio (OR) for the vomiting was not calculable. The exploratory univariate logistic regression analysis confirmed that fever ≥ 38.5 °C (OR = 5.0; 95% CI: 1.2/21.5; p = 0.03), ≥5% dehydration (OR = 8.4; 95% CI: 1.1/69.6; p = 0.04), CRP (OR = 1.1; 95% CI: 1.05/1.2; p = 0.01), and neutrophil levels (OR = 1.1; 95% CI: 1.01/1.3; p = 0.04) were all predictive factors of AKI. AKI can occur in 7.4% of patients with AA. Particular attention should be paid to the kidney health of patients with AA especially in the presence of vomiting, ≥5% dehydration, fever ≥ 38.5 °C, and high CRP and neutrophils levels.